Effect of carbon-layer rearrangement on one- and two-photon absorption properties in the alternative graphene-like hybrids – A theoretical investigation. (March 2017) - Zhang, Li; Zou, Lu-Yi; Guo, Jing-Fu; Feng, Ji-Kang; Ren, Ai-Min
Abstract: In this work, novel alternative graphene-like hybrids covalent with porphyrin (porphyrin-graphene-like hybrids) are designed, named TPP-gra(n)-a and TPP-gra(n)-b (n = 1–5), respectively. Moreover, the differences in their electronic structures, one-photon absorption (OPA) and two-photon absorption (TPA) properties are revealed by theoretical chemistry calculations. Our study shows that the rearrangement of carbon-atom layers of the hybrids can effectively enhance electronic delocalization, bringing about outstanding TPA properties. In addition to the increase of the graphene-like size, substituting porphyrin into different active-carbon of graphene-like molecules can cause better polarization of TPP-gra(n)-b series than TPP-gra(n)-a series, resulting in TPP-gra(n)-b series possess relatively higher TPA cross sections ( δ TPA ) than that of corresponding TPP-gra(n)-a compounds, such as TPP-gra3-b, TPP-gra4-b and TPP-gra5-b, whose δ TPA can be as large as 5686.2–19496.6 GM ranging from 535.8 to 579.4 nm. The carbon-based materials possessing relatively high δ TPA values have a great potential for applications in optoelectronic devices and optical limiting fields. Consequently, we expect the calculations can provide a theoretical perspective for further studies on TPA materials based on graphene. Graphical abstract: Highlights: The relationships between structures and OPA/TPA features of two series of porphyrin-graphene-like hybrids were analyzed. The rearrangement of the carbon-atom layer can enhance electronic delocalization. Introducing porphyrin into different active-carbon of graphene-like compounds results in different polarization.